1997
DOI: 10.5935/0305-7518.19970028
|View full text |Cite
|
Sign up to set email alerts
|

Women and leprosy: a review

Abstract: Summary Gender inequalities in health have a significant impact on women's health. In leprosy gender inequalities could be even more serious, as it is a highly stigmatized disease. A review has been made of the most recent literature dealing with gender and leprosy. First some data are presented on gender inequalities in rates of case detection, deformities and reversal reactions among leprosy patients. Then the major factors contributing to those differences are discussed. The paper ends with some recommendat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 3 publications
2
16
0
3
Order By: Relevance
“…In this context it is relevant that unemployment and illiteracy, both present to a greater extent in females, were independent predictor variables for the increased risk of undernutrition in the index case. Our ®ndings of increased illiteracy and unemployment in female leprosy patients is similar to that reported in literature (Le Grand, 1997). Family anthropometry has been recognized as an important strategy for determining community nutrition (Dugdale, 1985).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In this context it is relevant that unemployment and illiteracy, both present to a greater extent in females, were independent predictor variables for the increased risk of undernutrition in the index case. Our ®ndings of increased illiteracy and unemployment in female leprosy patients is similar to that reported in literature (Le Grand, 1997). Family anthropometry has been recognized as an important strategy for determining community nutrition (Dugdale, 1985).…”
Section: Discussionsupporting
confidence: 80%
“…Studies in rural Bangladesh have indicated that women consistently receive less of their energy requirements than either their children or their husbands (Kramer et al, 1997). This gender inequality is likely to be more pronounced in leprosy since women are believed to suffer the socio-cultural consequences of leprosy to a greater extent than men (Le Grand, 1997). It was our contention that the already disadvantaged woman in the household would be at further risk of undernutrition if she were not a wage earner.…”
Section: Discussionmentioning
confidence: 80%
“…This paper highlights the various aspects of leprosy in women in developing countries over the last few decades (Le grand, 1997), including prevalence, clinical features, complications, social aspects and treatment-related issues. It highlights that screening, treating, and rehabilitating women with leprosy is an important aspect of leprosy programs, and counseling women and their spouses and family members will go a long way in enabling female patients to return to their normal lives.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that more girls were examined in the study (51.5%) and seropositivity can vary according to the endemy 9 . It is important to remember that adult women are known seek out health services more often, a fact that may favor greater access to health services and thus to early leprosy diagnosis 9 .…”
Section: Discussionmentioning
confidence: 99%